Peningkatan Kualitas Pembelajaran Biologi Melalui Model Lesson Study Berbasis Deep Learning Approach Pada Guru SMK - Arum Sanjayanti; Ferry Fauzi; Kristiyanto Kristiyanto (Bioed : Jurnal Pendidikan Biologi, 2026)
This study aims to improve the quality of Biology education through the implementation of Lesson Study based on the Deep Learning Approach (DLA) with teachers in Vocational High Schools (SMK). The main problem in Biology education in SMK is the tendency of teachers to still apply learning strategies oriented toward surface learning, which emphasizes memorization of concepts and task completion without deep meaning. This study uses the Lesson Study approach with three main stages: Plan–Do–See, combined with the Deep Learning Approach strategy, which emphasizes reflective learning, critical thinking, and contextual learning. The subjects of this study consisted of 9 SMK teachers in Jakarta. The research method uses a collaborative Classroom Action Research (CAR) design, conducted in three cycles. Data was collected through observations, interviews, reflective journals from teachers, and an assessment of learning quality using the Lesson Observation Sheet and Deep Learning Rubric instruments. The results of the study show that there was an improvement in the pedagogical competence of Biology teachers in SMK, particularly in designing, implementing, and reflecting on deep learning approach-based lessons